2002
DOI: 10.4269/ajtmh.2002.66.622
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and ecologic characteristics of Bartonella communities in rodents in southern China.

Abstract: Abstract. Ecologic and bacteriologic observations of small mammals captured in Yunnan Province in the People's Republic of China indicated that Bartonella infections occurred at a high prevalence among some rodent species. Sequence analyses of the citrate synthase genes of these Bartonella demonstrated that rodents in this region harbored a diverse assemblage of strains. The Bartonella isolates obtained from Apodemus, Eothenomys, and Rattus typically clustered separately by genus of rodent host. Cultures obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
116
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 16 publications
8
116
0
4
Order By: Relevance
“…Previous investigations concerning Bartonella infections in rodents, cat fleas, and ticks have shown a high genetic diversity in Bartonella in Yunnan, China (Ying et al, 2002;Bai et al, 2005;Li et al, 2005). Our findings further confirm that there are different Bartonella genotypes in the rodents, and the rodent fleas can carry Bartonella in Yunnan Province.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous investigations concerning Bartonella infections in rodents, cat fleas, and ticks have shown a high genetic diversity in Bartonella in Yunnan, China (Ying et al, 2002;Bai et al, 2005;Li et al, 2005). Our findings further confirm that there are different Bartonella genotypes in the rodents, and the rodent fleas can carry Bartonella in Yunnan Province.…”
Section: Discussionmentioning
confidence: 97%
“…B. tribocorum is a rodent-associated species that is distributed widely and that has been isolated from R. norvegicus in Europe and North America (Heller et al, 1998;Ellis et al, 1999). Ying et al (2002) demonstrated a B. tribocorum bacteremia in R. norvegicus and R. tanezumi flavipectus in western Yunnan, China. Li et al (2004) reported a high prevalence of Bartonella (42.0%) from R. tanezumi flavipectus, with X. cheopis as dominant species (Guo et al, 2000), which inhabits indoor areas and courtyards, usually in south China, and is in close contact with human beings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations